Iecg 2018 2018
DOI: 10.3390/iecg_2018-05349
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Rare Earth Elements from Aqueous Solutions Using Geopolymers

Abstract: Rare earth elements, i.e., lanthanides, are important components of many recently developed technology applications. However, their increasing use in the industrial sector, medicine, and agriculture over the last few decades has provided them with the title of “new pollutants”. Different methods are now applied for the removal of various pollutants from wastewaters, whereby the emphasis is placed on adsorption due to its simplicity, high efficiency, and low cost. In the present study, geopolymers prepared from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Furthermore, the recycling of REEs from various end-of-life products is challenging. Fiket et al (2018) reported a preliminary study in which they adsorbed Ce, La, Nd, Pm, Dy, Er, Eu, Gd, Ho, Lu, Sc, Sm, Tb, Tm, Y, and Yb from multi-element solution (total concentration of REEs was 1 mg/L) on coal fly ash-geopolymer. Their results demonstrate that all studied REEs were adsorbed quite effectively when using contact time of 120 min and that the geopolymer SiO 2 /Na 2 O ratio of 0.7-0.8 was more efficient than 1.1-1.3.…”
Section: Preparationmentioning
confidence: 99%
“…Furthermore, the recycling of REEs from various end-of-life products is challenging. Fiket et al (2018) reported a preliminary study in which they adsorbed Ce, La, Nd, Pm, Dy, Er, Eu, Gd, Ho, Lu, Sc, Sm, Tb, Tm, Y, and Yb from multi-element solution (total concentration of REEs was 1 mg/L) on coal fly ash-geopolymer. Their results demonstrate that all studied REEs were adsorbed quite effectively when using contact time of 120 min and that the geopolymer SiO 2 /Na 2 O ratio of 0.7-0.8 was more efficient than 1.1-1.3.…”
Section: Preparationmentioning
confidence: 99%
“…These nanostructures enhance REE adsorption due to a larger area-to-volume ratio, porosity, stability, and reduced density. In this sense, some geopolymers that help to separate HREE and LREE help to remove REE from the bulk and can facilitate subsequent separation [92].…”
Section: Separation By Adsorptionmentioning
confidence: 99%